Survivorship and Severe Complications Are Worse for Octogenarians and Elderly Patients with Pelvis Fractures as Compared to Adults: Data from the National Trauma Data Bank - Amir Matityahu; Joshua Elson; Saam Morshed; Meir Marmor (Journal of Osteoporosis)
Purpose. This study examined whether octogenarians and elderly patients with pelvic fractures have a different risk of complication and mortality as compared to adults. Methods. Data was gathered from the National Trauma Data Bank from 2002 to 2006. There were 32,660 patients 18–65, 6,408 patients 65–79, and 5,647 patients ≥ 80 years old with pelvic fractures. Descriptive statistics and bivariate and multivariate analyses were performed with the adult population as a referent. Results. Multivariate analysis showed 4.7-fold higher odds of death and 4.57 odds of complications in the octogenarian group after a pelvic fracture compared to adults. The elderly had 1.81-fold higher odds of death and 2.18-fold higher odds of severe complications after sustaining a severe pelvic fracture relative to adults. An ISS ≥ 16 yielded 15.1-fold increased odds of mortality and 18.3-fold higher odds of severe complications. Hypovolemic shock had 7.65-fold increased odds of death and 6.31-fold higher odds of severe complications. Between the ages of 18 and 89 years, there is approximately a 1% decrease in survivorship every 10 years. Conclusions. This study illustrates that patients older than 80 years old with pelvis fractures have a higher mortality and complications rate than elderly or adult patients.